Strategi Pemanfaatan Kecerdasan Buatan dalam Pembelajaran Pendidikan Agama Katolik Tingkat SMA - Lay, Sergius; Kristiana Mendrofa; Martina Rosmaulina Marbun; Antonius P Sipahutar; Megawati Naibaho (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The use of Artificial Intelligence (AI) in education offers significant opportunities to transform learning processes, including in Catholic Religious Education (CRE) at the senior high school level. This article aims to identify effective and ethical strategies for integrating AI into CRE instruction by considering Catholic faith values and students’ character development. The study uses a qualitative literature review approach to analyze scholarly sources and current practices of AI application in education. Findings indicate that AI can enhance personalized learning, provide real-time feedback, and create more interactive and context-rich learning experiences. Practical implementations such as adaptive learning systems, chatbots, and AI-based simulations have shown positive impacts on students' comprehension. However, challenges including teacher readiness, technological infrastructure, and ethical concerns must be addressed seriously. Therefore, integrating AI in CRE must be done thoughtfully, responsibly, and in harmony with religious and moral contexts. With careful planning, AI can become a valuable tool to deepen students' faith understanding and support holistic character formation in the digital age.